Helical transition metal complexes:synthesis, characterization and asymmetric epoxidations. - Liu, Tingting (Kansas State University, 2011)
A series of chiral titanium and manganese complexes with helix-directing salen ligands have been prepared, characterized and studied. Their structures displayed as a chiral helical motif as expected. And it was also found that all M(salen) units were exclusively M-helimeric in the solid state, except Ti(cyclohexyl-benz[a]anthryl) as P-helix. This may be due to the energy difference between P and M helice, which enables crystal packing forces to control and drive the molecular structure. This is also in agreement with the previous computational studies that the M configuration predominates in THF solution. All metal centers adopt a cis-β octahedral geometry except in Mn(binapthyl-phenanthryl-salen). Most of M(salen) complexes in this work afforded μ–oxo dinuclear helicates, instead of the expected monohelicate, except Mn(binapthyl-phenanthryl-salen), which is bridged by a third salen ligand. The titanium salt affected the complex solution behavior. In the presence of Cl[superscript]-, only mononuclear species was found by ESI-MS, while both di- and mononuclear species was found in MeOH in the presence of –O[superscript]iPr. The NMR spectra of Ti(salen) indicated one major species with cis-β geometry exist in most solution, which could be monomer or dimer, except Ti(binapthyl-salen). No counterions have been found in the solid state of Mn(salen) complexes in this work, but they affected the ligand decomposition in the solution in Mn(binapthyl-phenanthryl-salen). The Mn(salen) complexes could effectively and enatioselectively catalyze the asymmetric epoxidation of somoe trans, cis and terminal olefin, and various oxidants were employed.
Keywords: Transition metal complex; Asymmetric epoxidation; Chemistry (0485); Inorganic Chemistry (0488)